Acute HIV infection (AHI): Trained Service Linkage Workers and fourth-generation Assay Significantly Shorten Time to Antiretroviral Therapy Initiation. (4th October 2017) - Smith, Daniel; Gao, Qianmiao; Miao, Hongyu; Gutierrez, Oswaldo; Martinez, Cecilio; Vigil, Karen; Utay, Netanya S; Arduino, Roberto
Abstract: Background: Identification and early initiation of antiretroviral therapy (ART) during acute HIV infection (AHI) can preserve the immune system, reduce HIV reservoir size, and prevent transmission. We aimed to characterize patients with symptomatic AHI and their linkage/retention to care in a county clinic. Methods: Retrospective chart review of 60 patients diagnosed with AHI from 7/2012 to 4/2017 at two county hospitals emergency departments in Houston, TX. We compared the interval between diagnosis and initiation of ART before and after implementation of an AHI protocol in 11/2014 comprised of trained service linkage workers and use of the fourth-generation Ag/Ab combination assay as newly recommended by the CDC in 6/2014. AHI was defined as 1) detectable HIV RNA or reactive fourth-generation Ag/Ab combination assay with non-reactive HIV-1 antibody, 2) reactive third-generation Ab assay and negative/indeterminate Western blot (WB), or 3) positive WB that is negative for p31 band. CDC and DHHS definitions were used for linkage to and retention to care respectively. Results: 10 patients were diagnosed prior to AHI protocol (25-month period) and 50 after (31-month period). 92% established care with 78% retention. Median age 34 years (IQR 25–42), with 78% men, 58% Hispanic, 36% Black non-Hispanic, 50% men having sex with men. Presenting symptoms include fever 78%, chills 47%, malaise/fatigue 47%, nausea 38%, sore throat 37%, and headache 37%. Physical exam findings include rash 20%, pharyngeal edema/erythema 14%, cervical lymphadenopathy 8%, and thrush 7%. Baseline median CD4+ T cell count was 205 cells/µL (IQR 123–350), median HIV RNA 4.75 x 10 6 copies/mL (IQR 1.1–10.0 x 10 6 ). 56% had leukopenia, 47% thrombocytopenia, 37% syphilis, 12% aseptic meningitis and 8% K103N mutation. Median time to ART initiation decreased from 17 days (IQR 11.75–23.5) to 7 days (IQR 4.0–13.25) after protocol implementation ( P = 0.011). Conclusion: Employing trained service linkage workers and the new CDC testing algorithm significantly decreased time to initiating ART, which may improve long-term outcomes in these patients. However, 14% of patients were lost to follow-up, highlighting the need for a strategy to maintain engagement of care. Disclosures: All authors: No reported disclosures.